Efektifitas Media Manipulatif untuk Meningkatkan Kemampuan Mengenal Nilai Tempat pada Anak Kesulitan Belajar Kelas IV di SD Negeri 09 Koto Luar Padang - Nika Sri Rahayu; Kasiyati (Ranah Research : Journal of Multidisciplinary Research and Development, 2020)
This study discusses the problems found at SD N 09 Koto Luar Padang, namely the learning difficulties of 10-year-old children in the ability to recognize place value. This study aims to reveal whether manipulative media can increase place value in children's learning difficulties. The method used is Single Subject Research (SSR) with an A-B-A design. Collect and measure all data in baseline condition one (A-1) continuously for four meetings. Intervention using manipulative media (B) was carried out for eight meetings. Provides a second baseline (A-2) for four meetings. Data collection techniques in this study by giving tests. Based on the results of data analysis on conditions that show an increase in the ability to know place value. Overlapping analysis data between conditions, at baseline (A-1) and intervention (B) is 0%, and overlapping data for baseline conditions (A-2) and intervention is 0%. Based on the results of data analysis, shows that manipulative media can improve the ability to know place value on children's learning difficulties.